Molecular characterisation and evolutionary relationships of a potyvirus infecting Crotalaria in Brazil - Brief report - Freitas, D. S.; Maia, Ivan de Godoy [UNESP]; Arruda, P.; Vega, J. (Springer, 2002)
The 3' terminal genomic region of a potyvirus causing mosaic disease in several Crotalaria species has been cloned and sequenced. Comparisons of the nucleotide and deduced amino acid (aa) sequences of the cloned cDNA with those from other potyviruses show that the Crotalaria-infecting virus (designated Crotalaria mosaic virus; CrMV) is closely related to Cowpea aphid-borne mosaic virus (CABMV). Maximum identity (95.4%) at the coat protein (CP) aa level was observed between CrMV and a Brazilian strain of CABMV. Phylogenetic analyses derived from the sequence alignments of the CP and 3' untranslated region confirmed the identification of CrMV as a strain of CABMV and the name CABMV-Cr is suggested.